Glass fiber reinforced PPS composite material as well as preparation method and application thereof
By introducing brominated polyphenylene ether into PPS materials and grafting reaction with perfluorochemical compound, and adding hexagonal boron nitride thermal filler and fluoro-containing silane coupling agent, the problem of leakage resistance of PPS materials in the electronic and electrical field is solved, and self-flame retardant and high CTI performance is achieved, which is suitable for automobiles and electronic and electrical components.
Patent Information
- Application Number
- CN202510634915.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-22
AI Technical Summary
The existing PPS materials have insufficient ability to resist leakage and traces in the electronic and electrical fields, which affects their application and may lead to performance and appearance problems during the modification process.
The brominated polyphenylene ether is grafted with perfluoro compound, hexagonal boron nitride thermal filler and fluoro-containing silane coupling agent are added, and PPS is modified by chemical grafting method to form a self-flame retardant and thermally conductive network structure, enhancing the bonding of glass fiber to the matrix, and improving the leakage resistance of the material.
It achieves self-flame retardant and excellent leakage resistance electrical trace index, which is suitable for automobiles and electronic appliances, and improves the thermal conductivity and overall strength and toughness of the material.
Smart Images

Figure BDA0005406403140000021 
Figure BDA0005406403140000071 
Figure BDA0005406403140000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a glass fiber reinforced PPS composite material and a preparation method and application thereof. Background Art
[0002] Polyphenylene sulfide resin (hereinafter referred to as PPS) is a semi-crystalline polymer formed by alternating benzene rings and sulfur atoms. This configuration and structural stability give it unique properties, such as good thermal stability, self-flammability, excellent mechanical properties, good chemical resistance, and low moisture absorption. This also makes it widely used in fields such as electronics, automobiles, aerospace, and military. In the application of electrical products, the surface of the material is contaminated or covered with water vapor, and it is exposed to high-voltage electric fields, which will cause corrosion of the insulating material and lead to loss of insulation properties. PPS itself has benzene rings, and the unstable free radicals in it break down. Its degradation products accumulate in the form of carbon to form conductive pathways, resulting in loss of insulation. Therefore, PPS has poor resistance to leakage tracking, which also limits its application in the field of electronics and electrical appliances.
[0003] CN114907696A improves the mechanical strength of the material by modifying the toughening agent with polystyrene, achieving a flexural modulus of up to 18,000 MPa. The modified magnesium hydroxide also improves the PPS resin's tracking resistance, reaching a maximum of 600V. Furthermore, the modified magnesium hydroxide exhibits stronger resin bonding and good dispersion. However, the decomposition temperature of the magnesium hydroxide approaches the processing temperature of the PPS resin, potentially causing decomposition during the production process, which can affect the product's performance and appearance.
[0004] CN116355410A utilizes a composite of polyphenylene sulfide resin and polyamide resin to improve the material's tracking resistance, as well as its tensile and notched impact strength. The CTI reaches a maximum of 450V, but falls short of 600V. In the 400V embodiment, the flame retardancy is HB grade. While maintaining a V-0 flame retardancy, the CTI is a maximum of 200V. Therefore, while this solution has some success in improving the CTI, it significantly impacts the flame retardancy, limiting its practical application.
[0005] CN112457670A proposes a hydrophobic, high-CTI polyphenylene sulfide composition with excellent dimensional stability, toughness, and high rigidity. A coupling agent is used to enhance the bond between the resin and glass fiber, thereby increasing mechanical strength. Fluorosilicone oil is also added to improve the material's tracking resistance, reaching up to 250V. However, the addition of fluorosilicone oil can cause surface defects such as flow marks on the finished product, limiting its use due to production yield constraints. Summary of the Invention
[0006] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a glass fiber reinforced PPS composite material and its preparation method and application. The glass fiber reinforced PPS composite material of the present invention has self-flaming retardancy and excellent leakage tracking index, and can be used in the fields of automobiles, electronic appliances, etc.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In one aspect, the present invention provides a glass fiber reinforced PPS composite material, wherein the raw materials for preparing the glass fiber reinforced PPS composite material include the following components in percentage by weight:
[0009]
[0010] In the raw materials for preparing the glass fiber reinforced PPS composite material of the present invention, the content of brominated polyphenylene ether can be 50%, 53%, 55%, 58%, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78% or 80%, the content of the perfluorinated compound can be 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, and the content of the catalyst can be 0.1%, 0.2%, 0.3%, 0.4%, 0.6%, 0.7%, 0.8%, 0.9%, 10.1%, 10.2%, 10.3%, 10.4%, 10.5%, 10.6%, 10.7%, 10.8%, 10.9%, 10.9%, 10. The content of the thermal conductive filler can be 3%, 5%, 8%, 10%, 12%, 14% or 15%, the content of the glass fiber can be 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38% or 40%, and the content of the coupling agent can be 2%, 3%, 4%, 5%, 6%, 7% or 8%.
[0011] Preferably, the brominated polyphenylene ether is prepared by activating polyphenylene ether with N-bromosuccinimide (NBS) to introduce bromine atoms into the benzene ring of PPS to generate brominated PPS (PPS-Br).
[0012] Preferably, the perfluorinated compound is any one of perfluorooctanol, perfluorooctanoic acid (PFOA) or perfluoropolyether (PTFE), or a combination of at least two thereof.
[0013] In the present invention, perfluorinated segments are grafted onto brominated PPS because the reaction with brominated PPS requires that the compound containing the perfluorinated segment possess corresponding active sites, such as carboxyl, hydroxyl, and amino groups. Therefore, perfluorooctanol and hydroxyl-terminated perfluoropolyether are used in the present invention to achieve the reaction, chemically grafting PPS onto the fluorinated segments through esterification / amidation / nucleophilic substitution reactions.
[0014] Preferably, the catalyst is selected from any one of magnesium oxide and other metal oxide catalysts, benzoyl oxide BPO, dicumyl peroxide DCP or di-tert-butyl peroxide DTBP.
[0015] Preferably, the thermally conductive filler is any one of aluminum nitride, boron nitride, aluminum oxide, zinc oxide or magnesium oxide, or a combination of at least two thereof, preferably boron nitride, and more preferably hexagonal boron nitride.
[0016] In the present invention, hexagonal boron nitride micron fillers are preferably added as nucleation points to induce crystallization. At the same time, the thermal conductive network structure of the component realizes heat transmission and dissipation, thereby improving CTI. Hexagonal boron nitride has a high thermal conductivity of about 33W / m·K, and its thermal conductivity is even better under high temperature conditions. When added to the matrix, it greatly improves the thermal conductivity of the material, reduces heat accumulation, and avoids high-temperature flashover-induced large-scale carbonization of the tree surface, which causes surface insulation failure. The selection of flaky hexagonal boron nitride can better form a uniform thermal conductive layer network structure, and the thermal conductivity is increased to 2.5-4W / m·K.
[0017] Preferably, the coupling agent is selected from a fluorinated silane coupling agent, and more preferably tridecafluorooctyl triethoxysilane (FAS). In the present invention, the glass fiber is treated with a silane coupling agent to enhance the binding property of the glass fiber to the matrix, enhance the interfacial compatibility, and make the composite material have better strength and toughness. The glass fiber is treated with a fluorinated silane coupling agent so that its surface contains fluorinated segments, which enhances the binding property with the fluorinated modified PPS material. At the same time, the introduction of fluorine atoms makes the overall matrix, the glass fiber and the PPS tightly covered under the fluorinated layer, which can enhance the electrical tracking resistance of the composite material.
[0018] Preferably, the raw materials for preparing the glass fiber reinforced PPS composite material further include other additives.
[0019] Preferably, the other additives include at least one of a toughening agent, a lubricant, an antioxidant and a heat stabilizer.
[0020] Preferably, the content of the toughening agent in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.2-5%, for example, 0.2%, 0.3%, 0.5%, 1%, 2%, 3%, 4% or 5%.
[0021] Preferably, the toughening agent is selected from common toughening agents in the art, including but not limited to maleic anhydride grafted toughening agents, acrylic toughening agents, etc. Preferably, the toughening agent is POE-g-GMA.
[0022] Preferably, the content of lubricant in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.1-2%, for example, 0.1%, 0.5%, 0.8%, 1.2%, 1.5%, 1.8% or 2%.
[0023] Preferably, the lubricant is selected from common lubricants in the art, including but not limited to graphite, molybdenum disulfide, polytetrafluoroethylene, silicone, polyimide or nanoparticles.
[0024] Preferably, the content of the antioxidant in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.2-1%, for example, 0.2%, 0.4%, 0.5%, 0.8% or 1%.
[0025] Preferably, the antioxidant is selected from hindered phenol antioxidants or phosphite antioxidants, such as antioxidant 1076, TAS-A, etc.
[0026] Preferably, the content of the heat stabilizer in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.2-1%, for example, 0.2%, 0.4%, 0.5%, 0.8% or 1%.
[0027] Preferably, the heat stabilizer is selected from any one or a combination of at least two of nano titanium dioxide, composite organic tin compounds, methyl tin mercaptide, nano montmorillonite, etc.
[0028] On the other hand, the present invention provides a method for preparing the glass fiber reinforced PPS composite material as described above, the preparation method comprising the following steps:
[0029] (1) using a perfluorinated compound to carry out a grafting reaction with brominated polyphenylene ether to obtain a fluorinated graft-modified polyphenylene ether;
[0030] (2) The fluorinated graft-modified polyphenylene ether obtained in step (1) is mixed with a thermal conductive filler, glass fiber, a coupling agent and a catalyst, extruded and granulated to obtain the glass fiber reinforced PPS composite material.
[0031] In the present invention, PPS is modified by fluorination grafting to maintain the self-flame retardant ability of the modified PPS. At the same time, the fluorinated structure can capture electrons, enhance electron transport, reduce failure behaviors such as flashover caused by charge accumulation, and enhance the CTI of the material.
[0032] The fluorine element has a large electronegativity, and CF can achieve high polarization. After grafting fluorine-containing segments, under high voltage, the CF structure can capture a large number of electrons, realize a good electron shielding layer, prevent the continuous internal accumulation of space charge, and avoid local flashover and breakdown caused by charge accumulation; the CF bond energy is large, 485KJ / mol, which is greater than the C-H bond energy of 410KJ / mol and the C-C bond energy of 368KJ / mol. Adjacent F atoms repel each other, so that they are not in the same plane, and can form a tight coating on the C atoms, thereby achieving internal protection and enhancing the heat resistance and chemical stability of the matrix; and the surface energy of fluorine atoms is very low, and the symmetrical structural arrangement greatly improves the hydrophobicity of the material and improves the ability of the material surface to resist dirt.
[0033] The present invention introduces fluorinated segments through a chemical grafting method. The brominated polyphenylene ether is first activated by activating the PPS resin. An electrophilic substitution reaction, such as bromination or nitration, is then used to introduce active groups at the ortho position of the sulfur atom. N-bromosuccinimide (NBS) is preferably used to introduce bromine atoms onto the benzene ring of PPS to produce brominated PPS (PPS-Br). The brominated polyphenylene ether is then functionalized to include groups reactive with the active sites of PPS. Perfluorooctanoic acid (PFOA) or perfluoropolyether (PTFE) is preferably reacted with PPS to chemically graft the PPS to the fluorinated segments.
[0034] Preferably, the grafting reaction in step (1) is carried out under the catalysis of a second catalyst.
[0035] Preferably, the second catalyst is selected from KI.
[0036] Preferably, the temperature of the grafting reaction in step (1) is 90-130°C, such as 90°C, 95°C, 100°C, 110°C, 120°C or 130°C, and the reaction time is 16-24 hours, such as 16 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0037] Preferably, the extrusion in step (2) is carried out in a twin-screw extruder.
[0038] Preferably, the extrusion temperature in step (2) is 285-320°C, for example, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C or 320°C, and the screw speed is 200-400rpm, for example, 200rpm, 250rpm, 300rpm, 350rpm or 400rpm.
[0039] On the other hand, the present invention provides the use of the glass fiber reinforced PPS composite material as described above in automobile interiors and electronic and electrical components.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The glass fiber reinforced PPS composite material of the present invention has the advantages of self-flaming retardancy and excellent anti-electrical tracking index, and can be applied to the fields of automobiles, electronic appliances, etc. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0043] The sources of raw materials used in the following examples and comparative examples are:
[0044] Preparation of brominated polyphenylene ether: Dissolve PPS in fuming sulfuric acid, heat in an oil bath at 120°C, and react for 5 hours. Cool to room temperature, add anhydrous ether, and filter. Purify with acetone for 8 hours and oven dry at 100°C to obtain sulfonated PPS. Add sulfonated PPS to DMSO and FeCl3, and react at 50°C for 10 minutes. Add a 2% by weight bromine-DMSO solution, and react for 2 hours. Wash with ethanol and dry to obtain the final brominated PPS.
[0045] Synthesis of perfluorooctanol: Perfluorooctanoic acid and a long-chain alcohol are reacted at 60°C, pH 5, for 5 hours. The pH is adjusted to 11 using sodium hydroxide or other solvents, and hydrolyzed to perfluorooctanol at room temperature for 3 hours.
[0046] Hydroxyl-terminated perfluoropolyether: MacLean, P910108-perfluoropolyether;
[0047] Fiberglass: Jushi, ECS301-AD;
[0048] Hexagonal boron nitride: Kaier Nanotechnology, KBN-50;
[0049] Toughening agent: POE-g-GMA, Dow Chemical, AC 3427
[0050] Lubricant: BASF IrgaSLUB 3900.
[0051] Antioxidants: Phosphites, Aidico, HP-10.
[0052] Example 1
[0053] The raw materials for preparing the glass fiber reinforced PPS composite material in this embodiment are shown in Table 1.
[0054] Its preparation method is:
[0055] (1) A perfluorinated compound (perfluorooctanol) is grafted with brominated polyphenylene ether in the presence of catalyst KI at a reaction temperature of 100°C for 12 hours to obtain a fluorinated graft-modified polyphenylene ether;
[0056] (2) The fluorinated graft-modified polyphenylene ether obtained in step (1) is mixed with a thermally conductive filler, glass fiber, a coupling agent, a toughening agent, a lubricant, an antioxidant, and a thermal stabilizer, and the mixture is added to a twin-screw extruder and extruded at 300° C. and a screw speed of 300 rpm, and granulated to obtain the glass fiber reinforced PPS composite material.
[0057] Example 2-13
[0058] The raw materials and weight percentages (the unit of the amount of each substance is %) used in Examples 2-13 are shown in Table 1. The preparation method is the same as that in Example 1 (wherein in Example 2, fluorooctanol is replaced by hydroxyl-terminated perfluoropolyether).
[0059] Table 1
[0060]
[0061]
[0062]
[0063] The applicant declares that the present invention uses the above-described embodiments to illustrate the glass fiber-reinforced PPS composite material, its preparation method, and its application. However, the present invention is not limited to the above-described embodiments, and this does not necessarily mean that the present invention must rely on the above-described embodiments for implementation. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for various raw materials in the present invention, addition of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.
Claims
1. A glass fiber reinforced PPS composite material, characterized in that: The raw materials for preparing the glass fiber reinforced PPS composite material include the following components in percentage by weight:
2. The glass fiber reinforced PPS composite material according to claim 1, characterized in that: The brominated polyphenylene ether is prepared by activating the polyphenylene ether with N-bromosuccinimide to introduce bromine atoms into the benzene ring of the polyphenylene ether to generate brominated polyphenylene ether; Preferably, the perfluoro compound is any one of perfluorooctanol, perfluorooctanoic acid or hydroxyl-terminated perfluoropolyether, or a combination of at least two thereof.
3. The glass fiber reinforced PPS composite material according to claim 1 or 2, characterized in that: The catalyst is selected from any one of metal oxide catalysts, benzoyl oxide, dicumyl peroxide or di-tert-butyl peroxide DTBP.
4. The glass fiber reinforced PPS composite material according to any one of claims 1 to 3, characterized in that: The thermally conductive filler is any one of aluminum nitride, boron nitride, aluminum oxide, zinc oxide or magnesium oxide, or a combination of at least two thereof, preferably boron nitride, and more preferably hexagonal boron nitride.
5. The glass fiber reinforced PPS composite material according to any one of claims 1 to 4, characterized in that: The coupling agent is selected from fluorine-containing silane coupling agents, and tridecafluorooctyltriethoxysilane is more preferred.
6. The glass fiber reinforced PPS composite material according to any one of claims 1 to 5, characterized in that: The raw materials for preparing the glass fiber reinforced PPS composite material also include other additives; Preferably, the other additives include at least one of a toughening agent, a lubricant, an antioxidant and a heat stabilizer; Preferably, the content of toughening agent in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.2-5%; Preferably, the toughening agent is selected from at least one of a maleic anhydride grafted toughening agent or an acrylic toughening agent; preferably, the toughening agent is POE-g-GMA. Preferably, the content of lubricant in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.1-2%; Preferably, the lubricant is selected from any one of graphite, molybdenum disulfide, polytetrafluoroethylene, silicone, polyimide or nanoparticles, or a combination of at least two thereof. Preferably, the content of antioxidant in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.2-1%; Preferably, the antioxidant is selected from hindered phenol antioxidants or phosphite antioxidants; Preferably, the content of the heat stabilizer in the raw materials for preparing the glass fiber reinforced PPS composite material is 0.2-1%; Preferably, the heat stabilizer is selected from any one of nano titanium dioxide, composite organic tin compounds, methyl tin mercaptide or nano montmorillonite, or a combination of at least two thereof.
7. The method for preparing a glass fiber reinforced PPS composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) using a perfluorinated compound to carry out a grafting reaction with brominated polyphenylene ether to obtain a fluorinated graft-modified polyphenylene ether; (2) The fluorinated graft-modified polyphenylene ether obtained in step (1) is mixed with a thermal conductive filler, glass fiber, a coupling agent and a catalyst, extruded and granulated to obtain the glass fiber reinforced PPS composite material.
8. The preparation method according to claim 7, characterized in that The grafting reaction in step (1) is carried out under the catalysis of a second catalyst; Preferably, the second catalyst is selected from KI; Preferably, the temperature of the grafting reaction in step (1) is 90-130° C., and the reaction time is 16-24 hours.
9. The preparation method according to claim 7, characterized in that The extrusion in step (2) is carried out in a twin-screw extruder; Preferably, the extrusion temperature in step (2) is 285-320° C., and the screw speed is 200-400 rpm.
10. Use of the glass fiber reinforced PPS composite material according to any one of claims 1 to 6 in automobile interiors and electronic and electrical components.
Citation Information
Patent Citations
Hydrophobic high-CTI polyphenylene sulfide composition as well as preparation method and application thereof
CN112457670A
Water-solubility polyphenylene sulfide and preparation method thereof
CN101885843A
Wear-resistant amphiphobic polyphenylene sulfide composite material and preparation method thereof
CN117050524A
Fluorocarbon polymer coating composition
GB1585644A